Der p 5 allergen from house dust mite: first epitope mapping of rabbit IgG blocking antibodies. (January 2019) - Lahiani, S.; Dumez, M.E.; Bitam, I.; Galleni, M.
Abstract: Der p 5 is one of the important house dust mite allergens in Algeria; this allergen is frequently recognized by patients with allergic asthma. However, there is no information on its IgG–binding epitopes. In the present study, rabbits were immunized with recombinant Der p 5 allergen, and serum samples were obtained. Recognition of linear IgG epitopes of Der p 5 was determined using synthesized peptides derived from the allergen sequence. The results showed that serum from immunized rabbits recognized three linear epitopes from Der p 5 ( 28 EDKKHDYQNEFDFLLMERIHEQIK 43 ), ( 37 IHEQIKKGELALFYLQEQ 55 ) and ( 92 LMQRKDLDIFEQYNLEMAKKS 112 ). More interestingly, we observed that the 92 L-S 112 amino acid sequence is well recognized by both IgE and IgG antibodies. Der p 5 stimulates the synthesis of specific IgG antibodies which recognize common but also novel epitopes compared to IgE antibody binding. Indeed, the potential to induce IgG antibodies can be used to inhibit human IgE binding to allergens which may be part of the mechanism of action of specific immunotherapy.